How does a non-linear fiscal reaction affect Croatia's fiscal sustainability under shifting fiscal policy regimes? - Bašić, Luka (Oeconomica Jadertina, 2025)
This paper examines the effects of a non-linear fiscal reaction on Croatia’s fiscal sustainability under shifting fiscal policy regimes. The findings confirm a non-linear relationship between the primary fiscal balance and public debt in the baseline model, whereas in the extended models this relationship generally becomes linear, depending on the set of variables considered. This demonstrates that, despite the prevailing linear nature of fiscal policy, policymakers’ fiscal responses are not necessarily homogeneous, as their impulses may vary substantially depending on public-debt thresholds. Moreover, the results corroborate the recessive and regressive character of indirect tax revenues and the progressive character of direct tax revenues. The output gap and direct tax revenues act as corrective stabilisers, exhibiting lower cyclicality and making a significant contribution to improving the State’s overall fiscal position during expansionary phases. Markov-switching models and robustness tests clearly indicate that Croatia predominantly pursues a restrictive and procyclical fiscal policy, and that the implementation of such a policy during recessionary and consolidation phases has further deepened the recession.
Keywords: Croatia; expansionary and restrictive fiscal policy; fiscal sustainability; procyclicality and countercyclicality; non-linear fiscal reaction